Corporate Environmental Management Systems and Outcomes: A Case Study of ISO 14001 Implementation in a Cable Manufacturing Company in Tema, Ghana - Nancy, Botchway; Shine Francis, Gbedemah (European Scientific Journal, ESJ, 2018)
The potential for the firm to improve its resource use especially energy management by using Environmental Management Systems (EMS) like ISO 14001 has been shown to be possible. Yet, no in-depth research has been conducted to explore this possibility in Ghana. The implementation of EMS integrates the corporate environmental management strategies and management commitment to sustainable development but most of the organisations in developing countries of West Africa are slow to adopt the management system. The aim of this paper is to assess the drivers, the competitive advantages of ISO 14001 EMS certification and the environmental impact of ISO 14001 EMS certification, in terms of energy consumption. Before and after methods of evaluation were used to analyse the data collected. Purposive sampling technique was used to administer questionnaires and interview guides to employees of the cable manufacturing firm. A review was also made of annual data for electricity consumption before and after ISO 14001 EMS certification. The findings indicate that the main driver of the ISO 14001 EMS certification by the firm is to take advantage of certification to expand its market share. It was also found out that reduction in potential environmental liability risks is the main competitive advantage of ISO 14001 EMS certification. In terms of energy consumption, the findings show that the firm is saving a lot of energy thus cost. It is recommended that more efforts should be made by the energy commission of Ghana through the provision of funds to firms who want to implement environmental management systems.